2012
DOI: 10.1016/j.ijgo.2012.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based newborn resuscitation among frontline providers in a low‐resource country

Abstract: Focused community-based resuscitation training and device delivery resulted in a significantly increased proportion of newborns receiving life-saving positive-pressure breaths, in addition to improved provider knowledge and confidence. Furthermore, the program demonstrated the establishment of an effective training infrastructure within a disrupted health system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…30,31,42,60 Five studies (55.6%) reported no improvement in mortality despite improvement in test scores and/or delivery room behavior. 18,37,62,64,73 However, 3 of these studies (33.3%) showed a decrease either in newborns classified as stillborn or in asphyxiarelated cause-specific mortality, suggesting the training programs had a positive impact. 18,37,73 …”
Section: Impact Of Theoretical Knowledge On Delivery Room Behaviors Amentioning
confidence: 96%
See 3 more Smart Citations
“…30,31,42,60 Five studies (55.6%) reported no improvement in mortality despite improvement in test scores and/or delivery room behavior. 18,37,62,64,73 However, 3 of these studies (33.3%) showed a decrease either in newborns classified as stillborn or in asphyxiarelated cause-specific mortality, suggesting the training programs had a positive impact. 18,37,73 …”
Section: Impact Of Theoretical Knowledge On Delivery Room Behaviors Amentioning
confidence: 96%
“…In 10 (62.5%) of these studies, examiners directly observed birth attendants, 18,30,31,36,43,44,59,64,65 whereas in 7 studies (43.8%), scores were based on chart review or recall by birth attendants and/or the newborn's mother. 37,43,47,50,57,60,62 One study both directly observed birth attendants and surveyed community women cared for by these attendants. 43 …”
Section: Description Of Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Our previous research analyzed the effectiveness of a newborn resuscitation training program conducted in Indonesia beginning in 2005. 9 The training program occurred in a disrupted health system after the 2004 Asian tsunami and resolution of the civil conflict in the province of Aceh, Indonesia. The study assessed two groups of midwives.…”
Section: Introductionmentioning
confidence: 99%